Comparative in vitro study of the cleaning efficacy of AirFloss ultra and I-Prox Sulcus brushes in an orthodontic phantom model - Hanna Boes (Nature Portfolio, 2021)
Abstract Preventing biofilm-related risks such as gingivitis and white spot lesions during orthodontic treatments is very challenging. The cleaning efficiencies of AirFloss Ultra and I-Prox P sulcus brushes were evaluated using an orthodontic phantom model. After attaching brackets onto black-coated maxillary KaVo teeth, a plaque substitute was applied. The evaluated tooth surfaces were divided into two areas. Cleaning was performed with an AirFloss Ultra with two (A-2) or four (A-4) sprays or an I-Prox P for two (I-2) or four (I-4) seconds. Images before and after cleaning were digitally subtracted, and the percentage of fully cleaned surfaces was determined (Adobe Photoshop CS5, ImageJ). Statistical analysis was performed by ANOVA and post hoc tests with Bonferroni correction (SPSS 25, p < 0.05). The mean values of total cleaning efficacy were 26.87% for I-2, 43.73% for I-4, 34.93%, for A-2 and 56.78% for A-4. The efficacy was significantly higher for A-4 than for A-2, I-4, and I-2. There were significant differences between the four groups. Repeated cleaning led to an improved result. Within the study limitations, the AirFloss Ultra with four sprays proved to be more efficient than the sulcus brush I-Prox P for cleaning.